Neuroticism and Resilience: The mediational role of Emotional Intelligence - Iliopoulos, Panagiotis (Psychology: the Journal of the Hellenic Psychological Society, 2019)
Psychological resilience refers to the capacity of individuals to cope with and successfully manage adversities. Given the links between Neuroticism as a personality dimension, Emotional Intelligence (EI) and Resilience, the present study examined the mediating role of EI in the relationship between Neuroticism and Resilience. The sample consisted mostly of undergraduate students (mean age = 20,55). The Big Five Inventory (BFI) (Benet- Martinez, 1998), the Greek Scale of Emotional Intelligence (GEIS) (Tsaousis, 2008) and the Resilience Scale (RS) (Wagnlid & Young, 1993) were administered to the participants (n = 123). Correlation analyses showed a significant negative correlation between Neuroticism and Resilience, as well as between Neuroticism and EI. Conversely, EI correlated positively with Resilience. As shown by the mediation analysis, ΕΙ constitutes a significant mediational factor in the relationship between Neuroticism and Resilience, suggesting that the aforementioned link is mainly due to the mediating effect of EI. In conclusion, the results demonstrate the crucial mediational role of emotion-related processes in the effect of personality on psychosocial adjustment, expanding pre-existing findings. However, further research is needed by using alternative methods and considering additional mediators and moderators.